2021
DOI: 10.2147/dmso.s289923
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Mass Index and Male Sperm Apoptosis and Apoptosis-Related Factors

Abstract: Background Although obesity may affect reproductive functions, the molecular mechanisms of apoptosis-related biomarkers remain uncertain. Objective To examine the effects of body mass index on sperm quality and apoptosis-related factors in seminal plasma of men. Methods Data for 54 subfertile men were collected at our reproductive medical center. The men were divided into normal weight, overweight, and obese groups based on their body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Thus, VEGF-A being present in the greatest concentrations within SP is not entirely surprising. Furthermore, research has demonstrated a decrease of VEGF-A in the SP of obese humans causing a negative effect on semen quality (Zhu et al, 2021). Our study agrees with these results since VEGF-A had one of the lowest VIP impacts of all the cytokines presented, more specifically during the LR and GO treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, VEGF-A being present in the greatest concentrations within SP is not entirely surprising. Furthermore, research has demonstrated a decrease of VEGF-A in the SP of obese humans causing a negative effect on semen quality (Zhu et al, 2021). Our study agrees with these results since VEGF-A had one of the lowest VIP impacts of all the cytokines presented, more specifically during the LR and GO treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors observed favourable effect of alcohol on semen parameter in moderate amount (22) Semen volume, sperm count, motility, and morphology are affected by alcohol(23). Sperm apoptosis was signi cantly increased in overweight and obese men compared with men with normal BMI (25). Alterations in morphology and decreased concentration, motility, and viability have been observed among smokers.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, high fat consumption reshapes the fatty acid composition of sperm by altering their metabolism in the testis (Andersen et al, 2016). Sperm DNA fragmentation is also increased in ejaculated semen of obese subjects (Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%